Efficiency and market analysis of bioenergy industry in EU28 region - Alsaleh, Mohammed (2017)
This thesis is motivated based on the production of bioenergy industry driven by its increasing the industry efficiency in European Union (EU) 28 region. In other regions of the world are already on the verge of reducing the consumption of traditional energy from fossil fuel and switching to much cleaner and healthier energy such as renewable and sustainable energy, considering the potential environmental, resource and economic effects it has. The National Renewable Energy Action Plan (NREAPs) has set a target for EU28 region to be achieved by end of 2020 as follows; reduce 20% of energy consumption from fossil fuel sources, reduce 20% of CO2 emission from energy use based on 1990 standard, increase 20% of energy consumption of renewable and sustainable sources, and increase energy efficiency. The bioenergy production in EU28 is on the increase and has been even projected to increase further in the coming decades. This calls for concern and research into the area, as the increase is accompanied by some challenges of bioenergy industry in EU28 region. These likely challenges, which are related to technical efficiency, cost efficiency and imbalance of bioenergy markets, will be the focus of our study. Therefore, this study specifically investigates the impact of the economic determinants on the technical efficiency of bioenergy industry as objective one. While the impact of economic determinants of cost efficiency on bioenergy industry in EU28 region will be investigated. As second objective. Also, the imbalance of bioenergy domestic and international markets due to bioenergy supply shortage and high import will be analyzed and forecasted as the third objective as well. The research used in first stage analysis the Data Envelopment Analysis (DEA) statistical method to measure the efficiency rate of Bioenergy industry of EU28 region. The DEA mathematical approach frames a frontier of the observation of input and output ratio through linear programming techniques. Second stage regression is employed to find the correlation between the efficiency and the related economic variables in EU28 Region for the period between 1990 and 2013. The present study collects data on the bioenergy industry from EU28 countries for the period between 1990 and 2013. The simultaneous equations model estimates the domestic and international market models indirectly by solving reduced-form equations. The research sample is EU28 region. The countries have been segregated based on the economic development status such as; developed or developing country during the period 1990-2013. Moreover, the research has estimated and applied forecasting analysis for the same samples of bioenergy market model for the period between 2014 and 2020. This research employed yearly base database extracted from World Bank and EUROSTAT related to different economic variables for supply, demand, import and export for a sample of 28 countries in EU Region. A panel data has been made for (23) years from 1990 to 2013. The data includes the total prices, quantities, and other economic variables related to supply, demand, import and export of bioenergy market. Results show that in developing countries the rates of technical efficiency and pure technical efficiency are higher than the rates of technical efficiency and pure technical efficiency in developed countries during the period between 1990 and 2013. On the other hand, scale efficiency mean in developed countries is higher that the rate of scale efficiency in developing countries for the period between 1990 and 2013. The results of second stage panel regression for the EU28 region during 1990- 2013 shows that technical efficiency has positive and significant correlation with capital, labour input, GDP, but not RIR. Results show that developing and developed countries have equal cost efficiency means in bioenergy industry. Moreover, in developing countries allocative efficiency mean is higher than the one in developed countries. Also, in developed countries technical efficiency mean is higher than the one in developing countries. The results of second stage panel regression for the EU28 region during 1990-2013 shows that cost efficiency has positive and significant correlation with capital input, GDP, but not RIR. The result shows that in bioenergy domestic market, domestic price has a negative correlation with domestic demand in the bioenergy market. Moreover, the domestic price and biomass harvest have a significant influence on the supply model. Both of GDP and export prices have main impacts on the export demand for bioenergy international market. Moreover, the exchange rate has a significant and positive influence on export demand. In international markets, competitive import prices have a primary role in the improvement of import demand in the bioenergy international market. The forecasting analysis has forecasted a heavy decline in the export demand trend during the period from 2014-2020. On the other hand, the results of the forecasting analysis for the period from 2014-2020 have forecasted little increases in domestic supply, domestic demand and import demand trends. The results of the impact of economic determinants on efficiency (technical and cost) in bioenergy industry reveal that internal specific factors (labour input, labour cost, capital and capital cost) significantly increase the efficiency of bioenergy industry in EU28. When the estimation included macroeconomics factors (GDP and real interest rate), efficiency of bioenergy industry has been found highly affected by the macroeconomics variables. This means that the economic and internal specific determinants of bioenergy industry could help to increase the efficiency significantly. On the impact of economic determinants on bioenergy market in EU28, the results show (through applying simultaneous equation model) that the bioenergy market has correlation with different economic determinants (real exchange rate, GDP, prices, and input cost). The economic determinants have positive relation with bioenergy supply (but not the domestic demand) in EU28 domestic market. Moreover, the economic factors have negative correlation with the domestic import (but not the export) in international market in EU28. The general findings suggest that increase the efficiency of bioenergy industry can lead to improve the bioenergy production and meet the set NREAP target by 2020. The policy recommendation from this study is that governments of EU28 countries should strengthen the fight against inefficiency and strive to make the modern form of bioenergy products available and affordable. The EU28 forecasting model pertaining to the bioenergy market has presented increases in the figures of supply, demand and imports of bioenergy products, which reasonable in order to achieve the NREAPs target by 2020. On the other hand, export levels are expected to decrease strongly in all market models, indicating to the actual actions of the EU28 region to increase domestic consumption of bioenergy production by 20% as confirmed to in the NREAPs. The finding reveal that the EU28 region has taken successful steps in the bioenergy industry in order to achieve the NREAPs target pertaining to a 20% increase in the production outputs of renewable energy by the end of 2020. Moreover, this may help to achieve the additional two NREAPs targets related to a 20% decrease in the consumption of traditional energy and a 20% decrease in CO2 emissions.